Efficient Synthesis of (R)-(+)-Perillyl Alcohol From (R)-(+)-Limonene Using Engineered Escherichia coli Whole Cell Biocatalyst - Sun, Chao; Zhang, Rubing; Xie, Congxia (Frontiers in Bioengineering and Biotechnology, 2022)
(R)-(+)-perillyl alcohol is a much valued supplemental compound with a wide range of agricultural and pharmacological characteristics. The aim of this study was to improve (R)-(+)-perillyl alcohol production using a whole-cell catalytic formula. In this study, we employed plasmids with varying copy numbers to identify an appropriate strain, strain 03. We demonstrated that low levels of alKL provided maximal biocatalyst stability. Upon determination of the optimal conditions, the (R)-(+)-perillyl alcohol yield reached 130 mg/L. For cofactor regeneration, we constructed strain 10, expressing FDH from Candida boidinii, and achieved (R)-(+)-perillyl alcohol production of 230 mg/L. As a result, 1.23 g/L (R)-(+)-perillyl alcohol was transformed in a 5 L fermenter. Our proposed method facilitates an alternative approach to the economical biosynthesis of (R)-(+)-perillyl alcohol.